Impact of LMXSC on organizational commitment and deviant behavior: The moderating effect of perceived leader status - Son, EunYul; Choi, MyoungOk; Park, DongGun (Korean Journal of Industrial and Organizational Psychology, 2011)
The purpose of this present study was to investigate the influence of LMXSC(Leader-Member exchange social comparison) on organizational commitment and deviant behavior in workplace. It was also tested whether perceived leader status moderates the relationship between LMXSC and organizational commitment and deviant behavior. Data were collected from 306 employees who were working in various organizations. The results showed that (a) LMXSC was positively related to the organizational commitment, (b) perceived leader status moderated the relationship between LMXSC and organizational commitment. The relationship between LMXSC and deviant behavior was, however, not significant. Moderating effect of perceived leader status on relationship between LMXSC and deviant behavior was not significant, either. Based on these results, implications of these findings, limitations and future study directions were discussed.